Evaluation of Yeast Fermented Poultry By-Product Meal in Nile Tilapia (Oreochromis niloticus) Feed: Effects on Growth Performance, Digestive Enzymes Activity, Innate Immunity, and Antioxidant Capacity - Dawood, Mahmoud A. O.; Magouz, Fawzy I.; Mansour, Mohamed; Saleh, Ahmed A.; Asely, Amel M. El; Fadl, Sabreen E.; Ahmed, Hamada A.; Al-Ghanim, Khalid A.; Mahboob, Shahid; Al-Misned, Fahad (Frontiers in Veterinary Science, 2020)
The aim of the present study was to examine the effects of dietary inclusion of fermented poultry by-product meal (FPBM) on growth performance, digestive enzymes activity, innate immunity and antioxidant capacity in Nile tilapia (Oreochromis niloticus). A basal diet containing fish meal and soybean meal was considered as a control (Con), and four other diets were produced by inclusion of 10, 20, 30 or 40 % FPBM (FPBM10, FPBM20, FPBM30 and FPBM40 diets). The experiment was done in triplicates (20 fish per replicate) and the fish were fed the test diets to visual satiety twice daily for 8 weeks. The groups of fish fed the FPBM10 and FPBM20 diets showed significantly (P<0.05) higher weight gain and specific growth rate, and lower feed conversion ratio than those fed the Con and FPBM40 diets. Moreover, inclusion of 40 % FPBM led to significant reduction of feed intake compared to the other treatments. FPBM at all the tested levels improved intestinal protease activity and lipase activity was enhanced at 10-30 % inclusion levels. Furthermore, the FPBM10 and FPBM20 groups revealed significantly higher amylase activity than the other treatments. The FPBM10 group exhibited significantly higher phagocytic activity than the control group and phagocytic index was enhanced by dietary inclusion of 10-30 % FPBM. However, inclusion of over 30 % FPBM led to significant reduction of lysozyme, phagocytic and bactericidal activities compared to the control group. Further, FPBM10 and FPBM20 diets increased the serum IgM levels, while NBT was significantly increased by feeding FPBM10 diet compared with FPBM30 and FPBM40 groups (P<0.05). The group fed the FPBM30 diet showed significantly higher glutathione peroxidase activity than the control group. According to the analysis of the data by the polynomial regression, the inclusion of FPBM at 11.17 to 25.14 % can be applied effectively in the diets of tilapia for better growth performance and health condition.